2016
DOI: 10.1111/acps.12679
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to violence, a risk for suicide in youths and young adults. A meta‐analysis of longitudinal studies

Abstract: Early exposure to IPV confers a risk of suicide attempts and particularly suicide death in youths and young adults. Future research should address the effectiveness of preventing and detecting early any type of IPV exposure in early ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
93
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 64 publications
6
93
0
6
Order By: Relevance
“…Prospective cohort studies and twin studies have demonstrated the unique impact of sexual abuse on suicide attempt and death among adolescents and young adults, independent of contextual factors such as parent and child characteristics and quality of family environment (e.g. Brown, Cohen, Johnson, & Smailes, 1999;Castellv ı et al, 2017;Fergusson, Boden, & Horwood, 2008;Fergusson, Horwood, & Lynskey, 1996;Nelson et al, 2002). Sexual abuse has been shown to have longerterm effects than physical abuse (Fergusson et al, 2008), another potent risk factor for suicidal ideation and attempt (Dunn, McLaughlin, Slopen, Rosand, & Smoller, 2013;Gomez et al, 2017).…”
Section: Environmental Risk Factors and Correlatesmentioning
confidence: 99%
“…Prospective cohort studies and twin studies have demonstrated the unique impact of sexual abuse on suicide attempt and death among adolescents and young adults, independent of contextual factors such as parent and child characteristics and quality of family environment (e.g. Brown, Cohen, Johnson, & Smailes, 1999;Castellv ı et al, 2017;Fergusson, Boden, & Horwood, 2008;Fergusson, Horwood, & Lynskey, 1996;Nelson et al, 2002). Sexual abuse has been shown to have longerterm effects than physical abuse (Fergusson et al, 2008), another potent risk factor for suicidal ideation and attempt (Dunn, McLaughlin, Slopen, Rosand, & Smoller, 2013;Gomez et al, 2017).…”
Section: Environmental Risk Factors and Correlatesmentioning
confidence: 99%
“…Interpersonal factors such as low social connectedness also have been related to the likelihood of suicidal ideation and behavior (Czyz, Liu, & King, 2012;Gunn, Goldstein, & Gager, 2018). Bully victims and perpetrators have reported an increased incidence of SAs (Borowsky, Taliaferro, & McMorris, 2013), and physical and sexual abuse have been prospectively associated with SAs (Castellv ı et al, 2017). Interpersonal conflicts and losses, and legal/ disciplinary problems are acute stressors associated with SAs and suicide (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence and young adulthood is a crucial developmental period with an increasing autonomy but is also subject to rapid psychological, biological and social changes. Such changes may make youths vulnerable to environmental stress (Aro et al, 1993) which may contribute to psychopathology, alcohol and drug misuse, and risk behaviors (Aro et al, 1993;Arpawong et al, 2015;Pelkonen and Marttunen, 2003), and thus increase suicide risk and repeated suicide-related thoughts and behaviors (Castellvi et al, 2016). SITBs are common in young people (Baetens et al, 2011), and 18% will repeat suicidal or nonsuicidal behavior within a year (Hawton et al, 2007), which is strongly linked to suicide death with 40-60% of those who die by suicide having self-harmed in the past (Owens et al, 2002).…”
Section: Introductionmentioning
confidence: 99%